(3eYQaI CfhGY Yde GdMOjK hHjGf CUhdg hbhGYOgs - (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s ((3CMeO Hf eMeO GdfSGN GdebQi s)
(3ChdgG (B:s
(3GdMeO ddg GdgGOi ef ESJgOGg , GdhGbi ef EJbGg s
(3BNQgG (B:s
(3hYHO GdQRGb UfYGfi HeG ai hddg SHMGfg GdMeO GdCJe Ydi eG CSHZ ef CaVGdg hZGjI eG jCed GdBedhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hJYdjbGJs
(3hGdChQGb GdCNjQg HNW eZGjQ HChdgG Jedc SfI (B887 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs